Social anxiety is associated with impaired memory for imagined social events with positive outcomes. Issue 4 (18th May 2020) - Romano, Mia; Tran, Emma; Moscovitch, David A.
ABSTRACT: Cognitive models of social anxiety disorder suggest that memory biases for negative social information contribute to symptoms of social anxiety (SA). However, it remains unclear whether memory biases in SA are related to social information, specifically, and if so, whether the valence of such information would moderate memory performance. In the present study, 197 community participants were randomised to imagine themselves as the central character in either 10 social or 10 non-social scenarios. In both conditions, half of the scenarios ended with objectively positive outcomes and half ended with objectively negative outcomes. Results demonstrated that higher trait SA was related to memory performance for social scenarios only, and in particular to poorer memory for social scenarios that ended positively. Thus, the impact of SA on memory performance depended on how social information was framed, with higher SA related to poorer memory for positive social experiences. These context-specific effects contribute to the growing literature on positivity deficits in SA.